Cover Feature: Race on High‐loading Metal Single Atoms and Successful Preparation Strategies (ChemCatChem 2/2022). Issue 2 (21st December 2021) - Sangkhun, Weradesh; Ponchai, Jitprabhat; Phawa, Chaiyasit; Pengsawang, Aniwat; Faungnawakij, Kajornsak; Butburee, Teera
Abstract : The Cover Feature illustrates the evolution of supported metal catalysts from conventional bulk and nanoparticle catalysts to single‐atom catalysts (SACs), and the race to develop SACs with richer active sites for the future era of single atom catalysis. In their Review, W. Sangkhun, J. Ponchai et al. demonstrated the research efforts to increase the density of active sites (metal loading) of SACs from <0.1 wt% in the pioneer works to >25 wt% in the recently reported one. The successful preparation strategies to achieve high metal‐loading SACs are highlighted, and the outlooks to further improve the quantity and quality of active sites in SACs are pointed out. More information can be found in the Review by W. Sangkhun, J. Ponchai et al.